“Oh Ai Yad…”: Dysarthria Speech Disorder of Luis in The Accessible Van Life Channel - Lathifah, Fatinatu (English Literature Study Program, 2022)
Several speech disorders can interfere with the listener’s understanding in people with dysarthria. Previous studies on dysarthria only cover the type and characteristics of speech. Therefore, an in-depth analysis is also needed of the phonological processes. This study aimed to find out the types of dysarthria and analyze the language disorders experienced by Luis on the YouTube channel The Accessible Van Life. This study focused on Luis as he was suffering from dysarthria caused by severe traumatic brain injury. The data of the study were in the form of utterances spoken by Luis on The Accessible Van Life YouTube channel. Duffy's theory (2013) was used to analyze the types of dysarthria. meanwhile, the analysis of language disorder was based on Lanier’s theory (2010), and the phonological processes was based on Waengler's theory (2012). The results of this study indicatde that there were four types of dysarthria experienced by Luis, namely hypokinetic, hyperkinetic, flaccid, and spastic. The main problem that caused Luis’s dysarthria was hypokinetic. In addition, Luis experienced language disorders in articulation, fluency, and voice, with the most crucial effect was on articulation damage. Furthermore, the most prominent phonological disorder in Luis’s speech was the final consonant syllable phonological disorder. Finally, the findings of the study can be used as a reference for further studies to understand the speech disorder of dysathria sufferers.